(untitled) (Academia Science Repository, 2023)
Assessment of the origin of prolonged diarrhea in young children presents great difficulties. There is an opinion that prolonged diarrhea in young children can be a manifestation of sepsis, which often leads to the appointment of repeated courses of antibiotics both enterally and parenterally. Due to the unresolved nature of this issue, the tactics of managing these patients, issues of hospitalization and medical examination have not yet been worked out.